2007
DOI: 10.1210/jc.2007-0231
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sex Hormone-Binding Globulin Levels in Healthy Children and Girls with Precocious Puberty before and during Gonadotropin-Releasing Hormone Agonist Treatment

Abstract: SHBG levels were strongly dependent on body composition and sex steroid levels in children with normal and precocious puberty. Studies on insulin sensitivity and SHBG in puberty are needed to better understand the interaction between body composition and gonadal maturation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 36 publications
(41 reference statements)
8
45
1
Order By: Relevance
“…In theory, lower SHBG levels may increase the bioavailability of sex steroid hormones to glandular breast tissue (37). In the present study, lower SHBG levels were found in the girls classified as overweight/obese by both BMI and BIA as previously reported (38). Higher prevalence of overweight and obesity, based on BMI percentile-for-age, was also found in the early compared late matured pubertal boys, despite similar prevalence of total body fat above 28%.…”
Section: Clinical Studysupporting
confidence: 83%
“…In theory, lower SHBG levels may increase the bioavailability of sex steroid hormones to glandular breast tissue (37). In the present study, lower SHBG levels were found in the girls classified as overweight/obese by both BMI and BIA as previously reported (38). Higher prevalence of overweight and obesity, based on BMI percentile-for-age, was also found in the early compared late matured pubertal boys, despite similar prevalence of total body fat above 28%.…”
Section: Clinical Studysupporting
confidence: 83%
“…Published data from Esoterix Labs (17) were used as normal reference ranges data for hormone levels in children, adolescents, and young adults except for AMH, inhibin B, and SHBG. Age appropriate control data for AMH, inhibin B, and SHBG were obtained from reference data in the literature (18)(19)(20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…Normal reference ranges for prolactin for girls and adult females, 3-24 ng/ml (18). Normal ranges for E 2 : prepubertal girls aged 1-10 years, !15 pg/ml; girls aged 10-14 years, 7-60 pg/ml; and adult females, 30-75 pg/ml (18,21,22). Normal values (range, mean) for AMH in girls: aged 0-1 year, 0.2-1.9, 0.66 ng/ml; 1-2 years, 0.2-3.9, 0.9 ng/ml; aged 4-6 years, 0.…”
Section: Androgensmentioning
confidence: 99%
“…Second, the influence of the duration and dose of VPA or CBZ therapy, the age, sex, seizure locus, seizure type, seizure control and concomitant use of antiepileptic drugs, including the previous antiepileptic drugs that the patients had used, on the BMI gap may not have been fully excluded, even though we adjusted for several potential confounding factors in the analyses. Regarding age, it has been reported that pre-pubertal males had significantly higher SHBG levels compared with similar-aged pre-pubertal females, and the SHBG levels declined with age in both sexes [10,12]. Third, because we could not obtain any data about the SHBG level before VPA therapy in the present study, we could not clarify whether the association between being overweight and a low SHBG level existed prior to the use of VPA.…”
Section: Discussionmentioning
confidence: 68%
“…clobazam, gabapentin, topiramate, zonisamide) as covariates, separately in the patients treated with VPA and CBZ (as reference). The interaction between the plasma SHBG levels and sex was also included as a covariate, because the SHBG levels were reported to be affected by the sex of the subject [10,12]. The data on the SHBG levels were converted into log 10 values to ensure the normality of distribution before the multiple linear regression model was employed.…”
Section: Introductionmentioning
confidence: 99%